Proteomic profile of seminal plasma and spermatozoa of donkeys of the Pêga breed and its relationship with assisted reproduction - Costa, Isabella Cristina Tolêdo Alves (2023)
Donkeys, along with their hybrids, mules and hinnies, resulting from breeding with mares, have a longstanding tradition of being used for labor-intensive tasks. Historically, these animals played pivotal roles in agriculture, warfare, trade, and transportation. However, with the advent of modernization, this dynamic has shifted. In Europe, these animals have become more popular as pets, and some species even faced the brink of extinction. In contrast, Brazil hosts a significant population of undomesticated donkeys, especially in the Northeast. Recently, the demand for donkeys has seen a resurgence, primarily in China, due to the consumption of their milk and meat. Assisted reproduction would be an advantageous approach, as it is more cost-effective and practical than maintaining animals in the field. However, when cryopreserved, donkey semen suffers a drastic decrease in its fertilization capabilities. The first chapter of this thesis delved into discerning the differences between the proteomic profiles of cryopreserved and non-cryopreserved sperm. In cryopreserved samples, proteins associated with infertility were identified, such as SERPINE2 and SERPINC1, both linked to the loss of sperm capacitation, and PLAU, associated with reduced motility. A high concentration of nucleoporins, related to neurodegenerative diseases, was also observed. In contrast, non-cryopreserved sperm displayed a proteomic profile primarily oriented towards energy production and metabolism, reflecting the energetic demands required for maintaining sperm motility and viability. In the second chapter, the proteomic profile of donkey seminal plasma was explored, emphasizing the identification of potential infertility biomarkers. Compared to existing literature, CRISP3 and HSP1 were identified, proteins previously linked to infertility in stallions. Also, CRISP1, PTP an PKA have potencial as biomarkers. The proteomic profile also highlighted proteins connected to energy production, metabolism, and reproduction, suggesting an influential role of seminal plasma proteins in sperm viability during the reproductive process of donkeys. Keywords: Donkeys. Seminal plasma. Proteomics. Assisted reproduction. Cryopreserved semen.